Model Tests and Analytical Studies on Performance of Areca Leaf Cells as Cellular Confinement in Soil. Issue 4 (4th July 2021) - Kolathayar, Sreevalsa; Aravind, C. A.; TG, Sitharam
ABSTRACT: In this paper, the possibility of using naturally available low-cost areca leaf sheaths as an alternative to the commercially available HDPE geocell has been explored by conducting the laboratory model footing tests on soft soils. The experimental results proved that the provision of areca leaf sheath as an alternative to the HDPE geocells as soil reinforcements improved the bearing capacity of the soil considerably. The bearing capacity of the soil reinforced with areca cell and areca grid was found to be increased by approximately 1.25 times compared with that of the soil reinforced with commercially available geocell and geogrid. The increase in bearing capacity of the soil reinforced with areca cell and areca grid was almost four times compared with that of unreinforced soil. The experimental results were found to be in accord with the analytical formulation considering the factors such as lateral support reaction, vertical stress distribution reaction and grid reaction.